Trophic structure of the avifauna of Mato Silva, fragment deciduous forest Chiapetta, Rio Grande do Sul - Jacoboski, Lucilene Inês; Santos, Eunice Frühling dos; Ramos, Nadiane Pillatt (Revista da Biologia, 2018)
Forest fragmentation results in structural and functional changes in forest environments, including the loss of resources and of specific bird species microhabitats, resulting in changes in the structure of bird communities. The objective of this study was to conduct an inventory of bird species and analyze their trophic structure in a forest fragment. Eighty seven species of birds were identified. The similarity index between the two-year studies was 65%. The trophic structure of the avifauna demonstrated the predominance of omnivorous species, which may indicate some level of depletion of the fragment. The species recorded here contribute to the knowledge of the distribution of these species in this region that is little studied.